INTERPRETATION OF THE SUBJECT OF PRIVATE INTERNATIONAL LAW IN RUSSIAN DOCTRINE - Alexandrovich Svirin, Yury; Aleksandrovich Gureev, Vladimir; Anatolevich Malcev, Vitalij; Nikolaevich Shestov, Sergej; Alexandrovich Gorbunov , Mikhail (Revista Gênero e Interdisciplinaridade, 2020)
Although the term "private international law" was introduced into the legal space back in the 19th century, there is no consolidated scientific definition of this legal entity in Russian and foreign doctrine. In the authors’ opinion, the essence of private international law is manifested through its subject. The article presents and analyzes various views on the subject of private international law and formulates its own definition of private international law. Methods: General scientific methods of cognition such as comparative and systematic analysis, synthesis, historical analysis, and scientific research of legal entity "private international law and its subject" are used in the article. The objective of the study: To investigate the category of private international law, the private international law subject, and the features and criteria of the private international law subject. Results: The authors conclude that the subject of private international law includes not only private law relations, but also public legal relations linked to private relations. The authors also prove that private international law does not fit into the traditional understanding of the sectoral division of Russian law, as it regulates not one homogeneous group of public relations but several different groups of relations (civil, family, labor, corporate, procedural, etc.).